CONFIRMATORY FACTOR ANALYSIS OF ANTECEDENTS LATENT VARIABLES AS AN IMPORTANT INSTRUMENT TO IMPROVE MARKETING PERFORMANCE OF JEMBERâS CIGAR - Kurniawan, Bagus Yudhia (JURNAL EKONOMI AKUNTANSI DAN MANAJEMEN, 2016)
Jember Regency expanses of land and the production of Besuki Na Oogst (BNO) tobacco, which tends to increase every year, but this is not matched by an increase in purchases of BNO tobacco by companies or exporters. The phenomenon of the increase in hectarage and production of BNO tobacco, is not offset by the purchase of BNO tobacco products (a decline in BNO tobacco purchases) will obviously reduce the volume of sales and lower the growth rate of Jemberâs cigar sales. The purpose of this study was to determine the relationship of each indicator with variable of creativity and innovation as antecedent variables which is an important instrument to improve marketing performance, with the method of maximum likelihood estimation (MLE) to estimate the model parameters. The analysis technique used in this study is a confirmatory factor analysis (CFA), a multivariate analysis method that can be used to test or confirm whether the measurement model that is built was accordance with hypothesized. The results showed that the perception of respondent research on creativity, innovation, and marketing performance of Bobin PTPN X industrial units is good. Most powerful indicator as a measure of creativity variable is motivation, while the weakest as a measure of creativity variable is a newness of the strategy. Most powerful indicator as a measure of innovation variable is the product innovation, while the weakest as a measure of innovation variable is the level of investment in innovation. Most powerful indicator as a measure marketing performance variable is customer growth rate, while the weakest as a measure marketing performance variable is sales growth rate. Â  Keywords :Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â  Confirmatory Factor Analysis, Antecedents Latent Variables, Marketing Performance, Jemberâs Cigar